The Cappadocian reshaping of metaphysics: relational being - Maspero, Giulio (Cambridge University Press, 2024)
"This book shows how the Church Fathers, especially the Cappadocians in the 4th century, rethought Greek metaphysics, in particular relation, an extremely topical category. It offers a perspective to those who study philosophy, particularly in Late-Antiquity, and to those who study patristics and systematic theology"--